ANALISA KONSUMSI PANAS PADA SISTEM KILN DI PABRIK II PT SEMEN BATURAJA Tbk - Putra, Rizkika; Abimanyu, Abraham; Safaruddin, Safaruddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The kiln system is one of the main process systems in terms of production at PT. Semen Baturaja Tbk. The kiln system consists of 3 units, namely the suspension preheater, rotary kiln and grate cooler. This process will produce a product in the form of clinker which is the main ingredient in the cement manufacturing stage. This process requires a large amount of energy so it is necessary to know the energy consumption analysis used so that energy use in production can be utilized as much as possible. This research was conducted on the kiln system in factory II of PT Semen Baturaja Tbk. Analysis of heat consumption is carried out by calculating heat efficiency. The calculation of heat efficiency in the kiln system can be carried out in two stages, namely by calculating the mass and calculating the heat. From the data in this article it is found that the highest heat efficiency value is 82.90% with an average heat efficiency value of 81.23%. This shows that the kiln system in factory II of PT Semen Baturaja Tbk. still feasible to use because of the heat loss tolerance of 12-22%.